Modulation of benzo[a]pyrene diolepoxide-DNA adduct levels in human white blood cells by CYP1A1, GSTM1 and GSTT1 polymorphism - Rojas, Margarita; Kopp-Schneider, Annette; Bartsch, Helmut (Carcinogenesis, 2000)
The modulation of benzo[a]pyrene diolepoxide (BPDE)-DNA adduct levels by polymorphisms in the CYP1A1, GSTM1 and GSTT1 genes was assessed in leukocytes of Caucasian males.